THEORETICAL AND METHODOLOGICAL BACKGROUND FOR TRAINING STUDENTS OF ENGINEERING SPECIALTIES IN FOREIGN COMMUNICATION ETIQUETTE - Marina I. Mezentseva (Advanced Engineering Research, 2012)
The conditions for developing the foreign language professional competence as the goal of training s t u dents of the non - language university are considered. They could help a prospective specialist to realize his potentia l through the co mmunicative role in the social interaction with partners.